2015
DOI: 10.1161/circresaha.116.302521
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in Cardiovascular Diseases

Abstract: RNAs, natural antisense transcripts and other long noncoding RNAs (lncRNAs). The present article will introduce noncoding RNA species and will summarize the current understanding of lncRNAs in cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
484
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(495 citation statements)
references
References 113 publications
(120 reference statements)
6
484
0
5
Order By: Relevance
“…Martianov et al 29) demonstrated that noncoding RNA could directly interact with the general transcription factor IIB and format a stable complex, which could dissociate the preinitiation complex and major promoter, thus decreasing dihydrofolate reductase gene expression. Wang et al 30) found that ncRNACCND1 could recruit an RNA-binding protein chain); (c) Intronic: stemming from the introns of the protein-coding genes; (d) Intergenic: located between two protein-coding genes [termed long intergenic noncoding RNAs (lincRNAs)]; and (e) Bidirectional: produced by the upstream sequence and the opposite direction of protein-coding genes 3,14) .…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Martianov et al 29) demonstrated that noncoding RNA could directly interact with the general transcription factor IIB and format a stable complex, which could dissociate the preinitiation complex and major promoter, thus decreasing dihydrofolate reductase gene expression. Wang et al 30) found that ncRNACCND1 could recruit an RNA-binding protein chain); (c) Intronic: stemming from the introns of the protein-coding genes; (d) Intergenic: located between two protein-coding genes [termed long intergenic noncoding RNAs (lincRNAs)]; and (e) Bidirectional: produced by the upstream sequence and the opposite direction of protein-coding genes 3,14) .…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Differential transcript variants have different regulations and biological properties suggest a complex mechanism of ANRIL, which makes its function poorly understood 3) . Jarinova et al 46) found that the levels of the short variants DQ485454 and EU741058 were increased and the long variant DQ485453 was decreased in the whole blood RNA from the carriers of the risk alleles.…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, more and more studies have found that lncRNA was a new regulatory factor in cardiovascular diseases 5. LncRNA Mhrt could antagonize the function of Brg1, a chromatin‐remodelling factor that is activated by stress to trigger aberrant gene expression and cardiac myopathy, protecting the heart from pathological hypertrophy 6.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced role for atherosclerotic disease burden rather than socalled vulnerable plaque in cardiovascular event prognosis, even in the case of non-obstructive CAD, also supports this hypothesis [5,6], and the disregulation of RNA expression in circulating cells appears to correlate with the burden of atherosclerosis [7,8]. In addition, extracellular RNAs, especially microRNAs, as well as long non-coding RNAs may also be of diagnostic utility [9,10]. Finally, recent analysis of the relative global importance of transcriptional and translational regulation of protein expression has suggested that the former has been underestimated in prior work and that transcriptional regulation accounts for a large majority of variation in the expressed genome, reinforcing the importance of examining RNA levels [11][12][13].…”
mentioning
confidence: 97%